Robot Control near Singularity and Joint Limit Using a Continuous Task Transition Algorithm. (10th October 2013) - Han, Hyejin; Park, Jaeheung
When robots are controlled in the task space, singularities and joint limits are among the most critical and difficult issues that can arise. In this paper, we propose a new approach for the robots to operate in the regions near singularities and joint limits using the operational space control framework. Specifically, a continuous task transition algorithm called the intermediate desired value approach is applied to the hierarchically structured controller in the operational space control framework. In this approach, new tasks are defined for dealing with singularities and joint limits, and the tasks are activated or deactivated using the continuous task transition algorithm to guarantee the continuous execution of the tasks during the execution of the main task. The proposed approach is implemented on a 6-DOF manipulator called Roman-MD. The experimental results demonstrate its performance near the singular regions and joint limits.